TALABALARDA TEXNIKALÍQ HÁM TEXNOLOGIYALÍQ KOMPETENCIYALARDÍ QÁLIPLESTIRIW USÍLLARÍ - Orınbetov, N.; Kamilova, M.; Allamuratova Х.; Xudaybergenova, D. (SCIENCE and SOCIETY, 2024)
This article provides information about the main tasks that require a special approach to the formation of technical and technological competences of future technology teachers. aimed at development, they were given recommendations on successfully solving the tasks of the modern educational process.